The Service of Trans Jatim Bus Transportation by means of Public Value Approarch - Rodiyah, Isnaini; Ikhtiarini, Eva Ilifiyah (Indonesian Journal of Public Policy Review, 2023)
This study investigates the public value of the Trans Java East bus rapid transit (BRT) system, implemented to address urban congestion in Indonesia. Employing descriptive research methods with data collected through observation, interviews, and literature review, the analysis finds that while Trans Java East meets public value criteria for accessibility, affordability, and comfort, it falls short in fully mitigating congestion. Recommendations for optimization include route expansion, improved integration with other modes of transport, and enhanced operational efficiency. The study concludes that regional BRT systems, despite limitations, offer attractive mobility alternatives and require continuous development to maximize their impact on urban transport challenges. Highlight : Reduces congestion: While not a complete solution, Trans Java East offers a more attractive alternative to private vehicles, potentially easing traffic in the region. Public service fulfillment: Launched by the East Java government, this bus service aims to address the need for reliable and accessible public transportation, fulfilling a crucial responsibility. Promising, but needs improvement: The research finds Trans Java East meets public value criteria in principle, but highlights areas for development, such as further optimization of routes and schedules Keywords: East Java Trans Bus, public value, congestion, accessibility, improvement